European round robin test on solar collectors and solar thermal systems - Fischer, S. (2012)
Within the European project QAiST (Quality Assurance in Solar Thermal Heating and Cooling Technology)a Round Robin test on solar collectors and solar thermal systems is carried out in the years 2010 and 2011. For two different collector types, one flat plate collector and one evacuated tubular collector with CPC reflector, thermal performance tests according to EN 12975-2 (EN 12975, 2006) are carried out by 12 different test institutes throughout Europe. The two different solar thermal systems, one thermosiphon system and one system with forced circulation are subject to a thermal performance test according to EN 12976-2 (EN 12976, 2006) and are tested by 9 different test institutes.In order to finish the Round Robin test within two years despite of the high number of participants, the following procedure was applied: Each participant received in the year 2010 samples of the two different collector types and of the two solar thermal system types respectively. After testing, the samples have been sent to the next test institute to be tested within the year 2011. Thus all institutes are testing identical collectors and system types taken out of the same production batch, however each unique collector or system is only tested by two institutes. For the first time Round Robin tests on solar thermal products are evaluated by an independent institute (Institut für Eignungsprüfung) using the acknowledged procedures for the evaluation of proficiency tests.This paper presents some of the midterm results of the Round Robin test in an anonymous and standardised way.